The Role of the Smart Learning Environment in Advancing the Smart Learning Process: Review - Faisal A S. K. al Naqbi, Wan Salmuni Wan Mustafa, and Rafiduraida Binti Abdul Rahman (International Journal of Advanced Science and Technology, 2020)
Currently, the educational organizations and institutions are very interested and engrossed by the change in how human’s perspectives are changing and run.  Education is always at the front line of all those aspects that humans are striving to achieve.  Smart technologies are being used to change the methodologies of the conventional educational aiming at enhancing the performance and the ability of learners to be familiar with the ever-changing world.  A new pedagogical approach that considers collaborative learning is being used under designing a smart learning environment (SLE) where information and communication technologies (ICT) and radio frequency identification (RFID)-based indoor positioning system were used to examine students’ perceptions and the involvement of groups into smart classroom.  This cannot be achieved without merging the interactive multimedia system, ubiquitous computing, and several handheld devices. The teacher role is no longer carrying the same picture in the eyes of learners and amazingly, the position of the teacher was found to increase the engagement and motivation of the students.  In smart learning, teaching and learning have to deconstruct as a condition for relevancy.  It is hoped that smart learning could result in enhancing the effectiveness and efficiency of learners while keeping education flexible and comfortable.  Internet, digital resources, classes online, and wireless networks are just possible foundations of smart learning.  Constructing a framework for smart learning should take new concepts such as instruction via class-based differentiated, collaborating using group-based, personalizing via individual-based, and mass-based generative learning.  It is worth to say that smart learning is a very complicated process which carried out with so many challenges and obstacles such are learners’ perception, cultural differences, and the basic preparation and training of teachers.